An observational retrospective audit of patients presenting to a private hospital group during specific timeframes before, during and after the comrades marathon over an 8- year period - Petrick, Friedrich Johann (University of the Witwatersrand, Johannesburg, 2023)
Introduction: This study examined the impact of the Comrades Marathon (CM) on the presentation of patients to the emergency departments (EDs) of a CM sponsoring private hospital group over an 8-year period. Methodology: A retrospective, quantitative secondary database analysis of all patients presenting to the designated EDs during 3 defined timeframes: a 48-hour weekend one week before the CM; a 48-hour period spanning over the CM; and a 48-hour weekend one week after the CM. Results: There was an increase in ED presentations during the CM timeframe compared to the weekends before and after the CM. There was a relatively greater increase in the CM female patient presentations (49.45%) compared to the registered number of female CM athletes (20%). All the EDs indicated an increased number of patient presentations during the CM “Up-run” years compared to the CM “Down-run” years (5 638 vs. 4 487, p-value 0.013). Musculoskeletal medical encounters appeared more common during the “Down-run” races (30.44% vs. 26.37%, p-value 0.318), with gastrointestinal (15.62% vs. 17.62%, p-value 0.043) and respiratory (11.99% vs. 13.25%, p-value 0.045) medical encounters more common during “Up-run” races. Fatigue (54.25% more common) and Electrolyte & Fluids (81.85% more common) medical encounters were common during the CM timeframe compared to both the Before and After timeframes. Conclusion: Epidemiologically, the CM “Up-run” and “Down-run” may present with two distinct clinical profiles, due to the different elevation nature of the CM, and not as a single race. Limitations related to the retrospective nature of this study makes comparability with other studies difficult.
A research report submitted in partial fulfilment of the degree of Master of Medicine in Emergency Medicine, to the Faculty of Health Sciences, School of Clinical Medicine, University of the Witwatersrand, Johannesburg, 2023
Keywords: Ultramarathon; Run; Running; Athlete; Para athlete; Sport medicine; Injuries; Emergency department; Prehospital; Medical field hospital; Medical tent; UCTD; SDG-3: Good health and well-being; SDG-4: Quality education